Climate and shared evolutionary history drive trait variation among species of Neotropical understory monocots - Eleinis Ávila‐Lovera; Oscar M. Vargas; Jennifer L. Funk; Kathleen M. Kay; Gregory R. Goldsmith (Ecosphere, 2024)
Abstract Environmental variation commonly drives functional trait diversity within species, among species, and across communities. Climate and shared evolutionary history can both influence trait–environment relationships. We studied variation in plant functional traits among closely related Costus species occurring across environmental gradients, the extent to which this variation occurs within single species, and how that variation may be influenced by shared evolutionary history. We measured leaf, aboveground stem, rhizome, and fine root traits of 17 species of Costus in eight sites in Costa Rica and Panama, which varied in elevation, temperature, and precipitation. We then assessed the relationships among traits and environmental variables and estimated the phylogenetic signal of the traits. We observed significant relationships between functional traits and climate. Stomatal conductance decreased, but stem density and rhizome dry matter content increased with decreasing mean annual temperature and precipitation seasonality in both cross‐species and single‐species analyses. This suggests that herbaceous species have a similar trade‐off between plant hydraulic efficiency and safety as found in woody plants. Mean annual temperature was a stronger driver of trait variation than mean annual precipitation. We also found phylogenetic signal in leaf and stem structural traits (i.e., closely related species are more similar than distantly related species), but not in physiological or belowground traits. Our results demonstrate significant trait variation within and among species of Costus, a widespread understory and herbaceous genus in the tropics, which is driven by both climate and shared evolutionary history.